Plant-based foods in Canada: information, trust and closing the commercialization gap. Issue 10 (7th October 2019) - Clark, Lisa Frances; Bogdan, Ana-Maria
Abstract : Purpose: Despite the growing awareness of links between meat consumption and human, animal and environmental health, consumption rates of protein rich plant-based foods (PBFs) in Canada remain relatively low. The purpose of this paper is to better understand how information sources and trust relate to PBFs in Canadians' diets, and how these variables may factor into closing the commercialization gap for PBFs in Canada. Design/methodology/approach: A geographically representative sample of Canadians ( n =410) participated in a 20-minute, online survey. The survey consists of 24 questions covering demographic characteristics, motivations behind current and future food choices, frequency of current PBF consumption, sources of information about PBFs and trust levels of these sources. Findings: Most Canadians get information about PBFs from labels, the internet and family and friends, but only half trust these sources to provide accurate information. Sources of information (e.g. licensed health care professionals) that rank high in trust are only consulted by a minority of respondents. Several information sources (e.g. family and friends) are associated with consumers' willingness to try new PBFs, whereas other sources (e.g. labels) are associated with Canadians being unlikely to try new PBFs. Originality/value: Understanding the patterns of where Canadians access information about PBFs and what sources of information are trusted can help to strategically place information about PBF qualities among select information sources and to remove some of the information barriers contributing to the PBF commercialization gap.